Regulation of iodide transportation by a plant secondary metabolite in SW1736 anaplastic thyroid cancer cell line - Shabnam Heydarzadeh; Ali Asghar Moshtaghie; Maryam Daneshpour; Mehdi Hedayati (Discover Oncology)
Abstract Aims and Background Owing to impaired iodine metabolism, anaplastic thyroid carcinoma, recognized as one of the most formidable malignancies, is resistant to radioiodine therapy. This study was conducted to determine the possible role of Genistein as plant secondary metabolite in understanding the effectiveness of this nutraceutical compound in modulating Sodium iodide symporter (NIS) expression and iodide uptake in the SW1736 anaplastic thyroid cancer cell linen. Material Methods Cell viability was assessed using the MTT assay, whereas cell apoptosis was assessed using a flow cytometry assay (Annexin V-FITC Apoptosis Detection kit). To determine iodide uptake by SW1736 cells, a Sandell–Kolthoff reaction-based spectrophotometric assay was performed. QRT-PCR and western blotting were used to measure NIS mRNA and protein levels in SW1736 cells. Results SW1736 cells exhibited time- and dose-dependent growth inhibition in response to Genistein treatment. QRT-PCR analysis revealed that NIS mRNA levels in the Genistein-treated group were significantly (p < 0.05) higher than those in the non-treated group. Accordingly, Western blot analysis revealed that SW1736 cells treated with Genistein expressed a high level of the NIS protein (p < 0.01). Compared with the control group, Genistein increased iodide uptake (p < 0.001) in the thyroid cancer cell line SW1736. Conclusion The expression of NIS and subsequent iodine uptake after Genistein treatment suggest that ATC cells may be becoming more like differentiated thyroid cells, which typically have higher iodine uptake capabilities. However, this redifferentiation does not directly correlate with an increase in sensitivity to radioactive iodine treatment.